RELATIONSHIP BETWEEN MOTIVATION OF CHILDREN AND YOUTH AND TIME SPENT IN FOOTBALL TRAINING (GRADE 5-9) - Kovaļovs, Atis; Fernāte, Andra; Slaidiņš, Kristaps; Vītoliņš, Kārlis; Gailītis, Dāvids Dāvis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The laws and regulations of Latvia on the professional education activity in football training state that as the age of the students increases, the number of contact hours per week that must be spent in football training also increases. Furthermore, scientific literature often mentions that as people age, their motivation to engage in physical activity and sports often decreases. The aim of this study was to determine the relationship between the motivation of children and youth for participation and time spent in football training in different age groups. Within the framework of the study, the opinion of the Ethics Commission of the Latvian Academy of Sport Education was received on the compliance of the survey with ethical norms, as well as the legal representative of each research participant had confirmed their participation in the study with a permission. As part of the study, 167 research participants from one Latvian school were surveyed in the grade groups from 5 to 9. The number of hours the research participants spend in football training sessions per year was determined, as well as their motivation to participate in the training. The results of the study showed that as the age of children and youth increases, they spend more time in football training sessions (p≤0.001), but their motivation decreases every year (p≤0.01).